Conjugated polymer, conjugated compound, electron-donating organic material, photovoltaic cell material and photovoltaic cell
Patent Information
- Application Number
- JP2023101482
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
【0017】 本発明によれば、開放電圧を向上させ得る共役系重合体、共役系化合物、電子供与性有機材料、光起電力素子用材料および光起電力素子を提供することができる。
Smart Images

Figure 2025001795000025 
Figure 2025001795000026 
Figure 2025001795000027
Abstract
Description
[Technical field]
[0001] The present invention relates to a conjugated polymer, a conjugated compound, an electron-donating organic material using the same, a material for a photovoltaic device, and a photovoltaic device. [Background technology]
[0002] Solar cells have attracted much attention as an energy source that contributes to the realization of a recycling-oriented society. Currently, inorganic materials such as single crystal silicon, polycrystalline silicon, amorphous silicon, and compound semiconductors are used as semiconductor materials for photovoltaic elements such as solar cells. However, solar cells manufactured using inorganic semiconductors have a drawback in that they are expensive to manufacture. The main reason for the high cost is the process of forming a semiconductor thin film under vacuum and high temperature. Therefore, organic solar cells using organic semiconductors such as conjugated polymers and organic crystals and organic dyes have been developed as semiconductor materials that are expected to simplify the manufacturing process. In such organic solar cells, the semiconductor material layer can be produced by a coating method, which greatly simplifies the manufacturing process.
[0003] However, organic solar cells using conjugated polymers have a lower photoelectric conversion efficiency than solar cells using conventional inorganic semiconductors, and therefore have not yet been put to practical use. Further improvement in the photoelectric conversion efficiency is essential for the practical use of organic solar cells.
[0004] To further improve the photoelectric conversion efficiency of organic solar cells, it is desirable to develop electron-donating organic materials that can increase the open circuit voltage, which is one of the device characteristics of solar cells. The open circuit voltage depends on the HOMO (Highest Occupied Molecular Orgital) level of the electron-donating material and the LUMO (Lowest Unoccupied Molecular Orbital) level of the electron-accepting material.
[0005] In order to increase the open circuit voltage, it is necessary for the electron donating material to have a deep HOMO level, and various heteroconjugated compounds in which nitrogen atoms or sulfur atoms are incorporated into a π-conjugated system to form a condensed ring have been reported as electron donating organic materials having such a deep HOMO level (for example, Patent Document 1). The organic solar cell element disclosed in Patent Document 1 exhibits favorable characteristics such as an open circuit voltage of 0.80 to 0.88 V and a photoelectric conversion efficiency of 11.6 to 14.9. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2023-31215 A Summary of the Invention [Problem to be solved by the invention]
[0007] For practical use of organic solar cells, increasing the voltage is essential to improve the energy conversion efficiency, and is also important for application to indoor photovoltaic and see-through organic thin-film solar cells. For this reason, electron-donating organic materials that exhibit a deeper HOMO level and contribute to further improvement of the open circuit voltage are desired.
[0008] The present invention has been made in consideration of the above-mentioned problems, and an object of the present invention is to provide a conjugated polymer, a conjugated compound, an electron-donating organic material, a material for a photovoltaic device, and a photovoltaic device, which are capable of improving an open circuit voltage. [Means for solving the problem]
[0009] The conjugated polymer according to the first aspect of the present invention comprises: Having a structure represented by formula 1: [ka] (In formula 1, R 1 R represents an alkyl group or an alkoxy group. 2 ~R 6may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkanoyl group, an alkoxycarbonyl group, a halogen, an aryl group, or a heteroaryl group. A represents an arylene group or a heteroarylene group. x and y may be the same or different and represent an integer of 0 to 4. When x or y is 2 or more, x R 3 and R 4 , y R 5 and R 6 may be the same or different. n indicates the degree of polymerization and is in the range of 2 to 1,000. It is characterized by:
[0010] In addition, in the formula 1, R 2 ~R 6 It is preferred that is hydrogen, a halogen or an alkyl group.
[0011] In addition, in the above formula 1, A preferably has a benzodithiophene structure.
[0012] The conjugated compound according to the second aspect of the present invention is Having a structure represented by formula 2: [ka] (In formula 2, R 7 R represents an alkyl group or an alkoxy group. 8 ~R 10 may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkoxycarbonyl group, a halogen atom, an aryl group, or a heteroaryl group. It is characterized by:
[0013] The electron donating organic material according to the third aspect of the present invention comprises: The present invention relates to a conjugated polymer comprising the conjugated polymer according to the first aspect of the present invention. It is characterized by:
[0014] A material for a photovoltaic device according to a fourth aspect of the present invention comprises: The present invention relates to a third aspect of an organic compound including an electron donor organic material and an electron acceptor organic material. It is characterized by:
[0015] The electron-accepting organic material may include a non-fullerene type electron-accepting organic material.
[0016] A photovoltaic element according to a fifth aspect of the present invention comprises: A photovoltaic element having at least an anode and a cathode, the photovoltaic element having an organic power generation layer between the anode and the cathode, the photovoltaic element having the material according to the fourth aspect of the present invention. It is characterized by: Effect of the Invention
[0017] According to the present invention, it is possible to provide a conjugated polymer, a conjugated compound, an electron-donating organic material, a material for a photovoltaic device, and a photovoltaic device, which are capable of improving the open circuit voltage. [Brief description of the drawings]
[0018] [Figure 1] 1 is a schematic cross-sectional view showing one aspect of a photovoltaic element according to an embodiment of the present invention. [Diagram 2] 1 is a graph showing the current density-voltage characteristics of the organic thin-film solar cell obtained in Example 1. [Diagram 3] 1 is a graph showing the spectral sensitivity characteristics of the organic thin-film solar cell obtained in Example 1. [Figure 4] 1 is a graph showing the current density-voltage characteristics of the organic thin-film solar cell obtained in Example 2. [Diagram 5] 1 is a graph showing the spectral sensitivity characteristics of the organic thin-film solar cell obtained in Example 2. [Figure 6] 1 is a graph showing the current density-voltage characteristics of the organic thin-film solar cell obtained in Comparative Example 1. [Figure 7] 1 is a graph showing the spectral sensitivity characteristics of the organic thin-film solar cell obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The conjugated polymer according to the present embodiment has a structure represented by formula 1. The conjugated polymer according to the present embodiment exhibits p-type semiconductor properties and can be used as an electron-donating organic semiconductor material (donor material).
[0020] [ka]
[0021] In formula 1, R 1 R represents an alkyl group or an alkoxy group. 2 ~R 6 may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkanoyl group, an alkoxycarbonyl group, a halogen, an aryl group, or a heteroaryl group. A represents an arylene group or a heteroarylene group. x and y may be the same or different and represent an integer of 0 to 4. When x or y is 2 or more, x R 3 and R 4 , y R 5 and R 6 may be the same or different, and n represents the degree of polymerization, which is in the range of 2 to 1,000.
[0022] In formula 1, the thienobenzobisthiazole skeleton in which thiophene is condensed to the benzobisthiazole skeleton has high planarity and improved packing, so that the carrier mobility in the thin film can be increased, and the short-circuit current and fill factor values can be increased. In addition, the thienobenzobisthiazole skeleton can introduce a bent structure into the polymer main chain while maintaining high planarity, so that the solubility in organic solvents can be improved. Furthermore, the nitrogen atom in the thienobenzobisthiazole skeleton in formula 1 has the effect of deepening the HOMO level of the conjugated polymer, and can improve the open circuit voltage of the photovoltaic element.
[0023] Furthermore, in the conjugated polymer having the structure represented by formula 1, an electron-withdrawing alkoxycarbonyl group or alkanoyl group is bonded to the thiophene ring of the thienobenzobisthiazole skeleton, and this further deepens the HOMO level, increasing the open circuit voltage of a photovoltaic element including a photoactive layer combined with an electron-accepting organic material, thereby improving the photoelectric conversion efficiency.
[0024] The alkyl group according to the present embodiment is, for example, a monovalent saturated aliphatic hydrocarbon group such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, or a dodecyl group, and may be linear, branched, or cyclic, and may be unsubstituted or substituted. Examples of the substituent in the case of substitution include an alkoxy group, an aryl group, a heteroaryl group, and a halogen, which will be described later. The number of carbon atoms in the alkyl group is preferably 4 or more, more preferably 6 or more, from the viewpoint of further improving the solubility of the conjugated polymer in an organic solvent. By improving the solubility of the conjugated polymer in an organic solvent, the conjugated polymer can be suitably applied to wet processes such as spin coating and slit coating. On the other hand, from the viewpoint of further improving the carrier mobility of the conjugated polymer and further improving the photoelectric conversion efficiency, the number of carbon atoms in the alkyl group is preferably 28 or less, more preferably 12 or less, and even more preferably 10 or less. In the present invention, the number of carbon atoms in each group does not include the number of carbon atoms contained in the substituent.
[0025] The alkoxy group according to the present embodiment refers to a monovalent aliphatic hydrocarbon group having an ether bond, such as a methoxy group, an ethoxy group, a propoxy group, or a butoxy group, and the aliphatic hydrocarbon group may be unsubstituted or substituted. In the case of substitution, examples of the substituent include an aryl group, a heteroaryl group, and a halogen, which will be described later. The preferred range of the carbon number of the alkoxy group is the same as that of the alkyl group described above.
[0026] The alkanoyl group according to the present embodiment refers to an alkyl group via a ketone group. The preferred range of the number of carbon atoms in the alkanoyl group is the same as that of the alkyl group described above.
[0027] The alkoxycarbonyl group according to the present embodiment refers to an alkyl group via an ester bond. The preferred range of the number of carbon atoms of the alkoxycarbonyl group is the same as that of the alkyl group described above.
[0028] The halogen in this embodiment is any one of fluorine, chlorine, bromine, and iodine.
[0029] The aryl group according to the present embodiment refers to a monovalent aromatic hydrocarbon group such as a phenyl group, a naphthyl group, a biphenyl group, a phenanthryl group, an anthryl group, or a terphenyl group, which may be unsubstituted or substituted. Examples of the substituent in the case of substitution include the above-mentioned alkyl group, alkoxy group, halogen, and the below-mentioned heteroaryl group. From the viewpoint of further improving the solubility and crystallinity of the conjugated polymer, the number of carbon atoms of the aryl group is preferably 6 or more and 12 or less.
[0030] The heteroaryl group according to the present embodiment refers to a monovalent heteroaromatic ring group having an atom other than carbon, such as a thienyl group, a furyl group, a pyrrolyl group, an imidazolyl group, a pyrazolyl group, an oxazolyl group, a pyridyl group, a pyrazyl group, a pyrimidyl group, or a thienothienyl group, and may be unsubstituted or substituted. In the case of substitution, examples of the substituent include the above-mentioned alkyl group, alkoxy group, halogen, and aryl group. From the viewpoint of further improving the solubility and crystallinity of the conjugated polymer, the number of carbon atoms of the heteroaryl group is preferably 4 or more and 6 or less.
[0031] R in Equation 1 3 ~R 6 R is preferably hydrogen or an alkyl group, and at least a part of R is preferably an alkyl group in order to improve the solubility in an organic solvent while maintaining the planarity of the conjugated polymer. 2In order to maintain planarity, hydrogen or halogen, which has a small atomic radius, is preferably used for R. 2 ~R 6 When represents an alkyl group, it preferably has 4 or more and 28 or less carbon atoms, more preferably 6 or more and 12 or less carbon atoms, and particularly preferably 7 or more and 10 or less carbon atoms.
[0032] In the above formula 1, x and y represent the number of thiophene rings, may be the same or different, and represent an integer of 0 to 4. In order to increase the planarity of the conjugated polymer to further improve carrier mobility and further increase photoelectric conversion efficiency, it is preferable that x and y are 1.
[0033] In the above formula 1, A represents an arylene group or a heteroarylene group. The arylene group according to the present embodiment refers to a divalent aromatic hydrocarbon group, and the heteroarylene group refers to a divalent heteroaromatic ring group having an atom other than carbon. The arylene group may be a divalent group corresponding to the aryl group exemplified above, and the heteroarylene group may be a divalent group corresponding to the heteroaryl group exemplified above. These may be unsubstituted or substituted. In order to increase the planarity of the conjugated polymer and improve the carrier mobility, A is preferably a heteroarylene group having a benzodithiophene ring. As the substituent on the benzodithiophene ring, a thienyl group that can further increase the planarity is particularly preferably used. Here, when the thienyl group is present on the benzodithiophene ring, the thienyl group preferably has a substituent, and the substituent may be an alkyl group or a halogen. The number of carbon atoms in the alkyl group is preferably 4 to 28 in order to achieve both solubility and planarity, and more preferably 6 to 12 inclusive. As the halogen, fluorine having a small atomic radius is preferably used in order to maintain planarity. As the substituent on the benzodithiophene, a thienyl group substituted only with an alkyl group is particularly preferably used since this reduces the number of synthesis steps.
[0034] In the above formula 1, n indicates the degree of polymerization and is an integer ranging from 2 to 1,000. From the viewpoint of further improving the carrier mobility of the conjugated polymer, and further improving the photoelectric conversion efficiency by more easily forming an effective carrier path in the bulk heterojunction type power generation layer, n is preferably 5 or more. On the other hand, from the viewpoint of ease of synthesis, n is preferably less than 200. Here, the degree of polymerization n can be determined from the weight average molecular weight. The weight average molecular weight can be determined by measuring using GPC (gel permeation chromatography) and converting it into a polystyrene standard sample.
[0035] Specific examples of the structure represented by formula 1 include the following structures.
[0036] [ka]
[0037] The conjugated polymer having the structure represented by formula 1 can be synthesized from the corresponding monomer by a polymerization reaction such as Stille coupling, for example, by a method similar to the method described in WO 2019 / 023025.
[0038] As a monomer corresponding to the conjugated polymer having the structure represented by formula 1, a conjugated compound having the structure represented by formula 2 below can be mentioned.
[0039] [ka]
[0040] In the above formula 2, R 8 ~R 10 R may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkoxycarbonyl group, a halogen atom, an aryl group, or a heteroaryl group. 7 is R in Eq. 1 Corresponding to R 8 is R in Eq. 2 Corresponds to.
[0041] The monomer represented by formula 2 can be synthesized with reference to the Examples described below.
[0042] The electron-donating organic material according to the present embodiment includes a conjugated polymer having a structure represented by the formula 1. The electron-donating organic material using the conjugated polymer having a structure represented by the formula 1 exhibits p-type semiconductor characteristics. In addition to such an electron-donating organic material, other electron-donating organic materials may be included.
[0043] The electron-donating organic material according to the present embodiment can be applied to organic transistors by taking advantage of its high carrier mobility. It can also be applied to various photoelectric conversion devices that utilize its photoelectric conversion function, optical rectification function, and the like. For example, it is useful for photovoltaic elements (solar cells), electronic elements (image sensors, optical sensors, optical switches), optical recording materials (optical memories, etc.), imaging elements, and the like, and can be particularly suitably used as a material for photovoltaic elements.
[0044] The material for a photovoltaic device according to the present embodiment includes the above-described electron donating organic material according to the present embodiment and an electron accepting organic material. The electron accepting organic material preferably exhibits n-type organic semiconductor properties.
[0045] Examples of electron-accepting organic materials that exhibit n-type semiconductor properties include phenyl C61 butyric acid methyl ester (PC 60 BM) and phenyl C71 butyric acid methyl ester (PC 70Fullerene-type organic materials such as 2,2'-((2Z,2'Z)-((12,13-bis(2-ethylhexyl)-3,9-(2-butyloctyl)-12,13-dihydro-[1,2,5]thiadiazolo[3,4-e]thieno[2”,3”:4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-d iyl)bis(methanylylidene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile (hereinafter referred to as L8 -BO) o[2”,3”:4',5']thieno[2',3':4,5]pyrrolo[3,2-g]thieno[2',3':4,5]thieno[3,2-b]indole-2,10-diyl)bis(methanylyl idene))bis(5,6-difluoro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile (hereinafter referred to as Y6) and 2,2'-[[6,6,12 Examples of non-fullerene organic materials include 12-Tetrakis(4-hexylphenyl)-6,12-dihydrodithieno[2,3-d:2',3'-d']-s-indaceno[1,2-b:5,6-b']dithiophene-2,8-diyl]bis[methylidyne(3-oxo-1H-indene-2,1(3H)-diylidene)]]bis[propanedinitrile] (ITIC).
[0046] The electron-donating organic material according to the present embodiment is preferably combined with a non-fullerene type electron-accepting organic material having a band gap of 1.2 eV to 1.7 eV, and since it can absorb solar energy in a wider wavelength range than a fullerene type electron-accepting organic material, it is possible to further improve the photoelectric conversion efficiency.
[0047] In the photovoltaic device material according to this embodiment, the content ratio of the electron donating organic material to the electron accepting organic material (donor-acceptor ratio) is preferably in the range of 1:99 to 99:1, and more preferably in the range of 20:80 to 60:40.
[0048] In order to further improve the photoelectric conversion efficiency, it is preferable to remove impurities that may become carrier traps as much as possible. In the present invention, examples of methods for removing impurities from the electron donating organic material and the electron accepting organic material include column chromatography, recrystallization, sublimation, reprecipitation, Soxhlet extraction, molecular weight fractionation by GPC, filtration, ion exchange, and chelate methods. Two or more of these methods may be combined.
[0049] Next, the photovoltaic element according to the present embodiment will be described. The photovoltaic element according to the present embodiment has at least an anode and a cathode, and has an organic semiconductor layer containing the material for photovoltaic elements according to the present embodiment between them. A hole transport layer may be provided between the organic semiconductor layer and the anode, or an electron transport layer may be provided between the organic semiconductor layer and the cathode. FIG. 1 shows a schematic cross-sectional view of one aspect of the photovoltaic element according to the present embodiment. On a substrate 1, an anode 2, an organic semiconductor layer 3 containing the material for photovoltaic elements according to the present embodiment, and a cathode 4 are provided in this order. Also, contrary to FIG. 1, a cathode / an organic semiconductor layer containing the material for photovoltaic elements according to the present embodiment / an anode may be provided on a substrate in this order.
[0050] Next, each layer will be described. The organic semiconductor layer includes the photovoltaic element material according to the present embodiment. That is, it includes an electron donating organic material using a conjugated polymer having a structure represented by formula 1, and an electron accepting organic material. These materials may be mixed or laminated, but it is preferable that they are mixed. A bulk heterojunction type organic semiconductor layer in which the electron donating organic material and the electron accepting organic material that contribute to photoelectric conversion are mixed to increase the interface between the electron donating organic material and the electron accepting organic material is preferable because it has excellent charge separation ability and charge transport ability. In the organic semiconductor layer that is a bulk heterojunction type organic power generation layer, it is preferable that the electron donating organic material and the electron accepting organic material are phase-separated at a nanometer size, and a carrier path to the electrode is formed in a co-continuous manner. The domain size of this phase separation structure is not particularly limited, but is usually 1 nm or more and 50 nm or less.
[0051] In the photovoltaic element according to the present embodiment, it is preferable that the anode or cathode has light transmittance, that is, is transparent or semitransparent. The light transmittance of the electrode is not particularly limited as long as it is sufficient for incident light to reach the organic semiconductor layer and generate an electromotive force. Here, the light transmittance in the present invention is defined as the transmitted light intensity (W / m 2 ) / incident light intensity (W / m 2 The thickness of the electrode is within a range that allows light transmission and electrical conductivity, and is preferably 20 nm to 300 nm, although it varies depending on the electrode material. The other electrode does not necessarily need to be light transmissive as long as it has electrical conductivity, and there is no particular limitation on the thickness.
[0052] Examples of conductive materials for forming electrodes include metals such as gold, platinum, silver, copper, iron, zinc, tin, aluminum, indium, chromium, nickel, cobalt, scandium, vanadium, yttrium, cerium, samarium, europium, terbium, and ytterbium, and alloys thereof; metal oxides such as indium, tin, molybdenum, and nickel; composite metal oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), aluminum zinc oxide (AZO), and gallium zinc oxide (GZO); alkali metals or alkaline earth metals such as lithium, magnesium, sodium, potassium, calcium, strontium, and barium; graphite, graphite intercalation compounds, carbon nanotubes, and graphene; and organic compounds such as polyaniline and its derivatives, and polythiophene and its derivatives. Two or more of these may be used, and electrodes made of these laminates are also preferably used.
[0053] Here, the conductive material used for the anode is preferably one that forms an ohmic junction with the organic semiconductor layer. Furthermore, in the case where a hole transport layer is used, the conductive material used for the anode is preferably one that forms an ohmic junction with the hole transport layer. Moreover, the conductive material used for the cathode is preferably one that forms an ohmic junction with the organic semiconductor layer or the electron transport layer. Here, an electron extraction layer may be introduced into the cathode, which can improve the junction between the cathode and the organic semiconductor layer or the electron transport layer and increase the extraction current. Therefore, the photoelectric conversion efficiency can be further improved. Examples of materials for forming the electron extraction layer include metal fluorides such as lithium fluoride (LiF) and cesium fluoride.
[0054] The substrate may be a substrate on which an electrode material or an organic semiconductor layer can be laminated depending on the type and application of the photoelectric conversion material, and examples of the substrate include films or plates made by any method from inorganic materials such as alkali-free glass, quartz glass, and alloys of aluminum, iron, copper, stainless steel, etc.; and organic materials such as polyester, polycarbonate, polyolefin, polyamide, polyimide, polyphenylene sulfide, polyparaxylene polymethyl methacrylate, epoxy resin, fluorine-based resin, etc. When light is incident from the substrate side, the substrate preferably has a light transmittance of 80% or more.
[0055] Examples of materials for forming the hole transport layer include conductive polymers such as polythiophene polymers, poly-p-phenylenevinylene polymers, polyfluorene polymers, polypyrrole polymers, polyaniline polymers, polyfuran polymers, polypyridine polymers, and polycarbazole polymers; low-molecular-weight organic compounds exhibiting p-type semiconductor properties, such as phthalocyanine derivatives (H2Pc, CuPc, ZnPc, etc.), porphyrin derivatives, and acene compounds (tetracene, pentacene, etc.); carbon compounds such as graphene and graphene oxide; and molybdenum oxides such as MoO3 (MoO x ), tungsten oxide such as WO3 (WO x ), nickel oxides such as NiO (NiO x ), vanadium oxides such as V2O5 (VO x ), zirconium oxide such as ZrO2 (ZrO x ), copper oxides such as CuO (CuO x ), copper iodide, ruthenium oxide such as RuO4 (RuO x ), rhenium oxides such as Re2O7 (ReO x ) and other inorganic compounds. Two or more of these may be used, or these may be laminated. Among these, polythiophene-based polymers such as polyethylenedioxythiophene (PEDOT) and PEDOT with polystyrene sulfonate (PSS), molybdenum oxide, vanadium oxide, and tungsten oxide are preferably used. The thickness of the hole transport layer is preferably 10 nm or more and 200 nm or less.
[0056] The material for forming the electron transport layer is preferably a material exhibiting n-type semiconductor properties, and titanium oxide such as TiO2 (TiO x ) and zinc oxide such as ZnO (ZnO x Inorganic materials such as PEI (Polyethylenimine), PDINO (2,9-bis[3-(dimethyloxidoamino)propyl]anthra[2,1,9-def:6,5,10-d'e'f']diisoquinoline-1,3,8,10(2H,9H)-tetrone), poly[[2,7-bis(2-ethylhexyl)-1,2,3,6,7,8-hexahydro-1,3,6,8-tetraoxobenzo[lmn][3,8]phenanthroline-4,9-diyl]-2,5-thiophenediyl[9,9-bis[3'((N,N-dimethyl)-N-ethylammonium)]-propyl]-9H-furan, Organic materials such as poly[[2,7-bis(2-ethylhexyl)-1,2,3,6,7,8-hexahydro-1,3,6,8-tetraoxobenzo[lmn][3,8]phenanthroline-4,9-diyl]-2,5-thiophenediyl[9,9-bis[3-(dimethylamino)propyl]-9H-fluorene-2,7-diyl]-2,5-thiophenediyl] (PNDIT-F3N); and organic-inorganic hybrid materials such as PEI-Zn (Polyethyleneimine-Zn) are preferably used.
[0057] Next, an example of a method for manufacturing a photovoltaic element according to the present embodiment will be described. A transparent electrode such as ITO (corresponding to the anode in this case) is formed on a substrate by sputtering or the like. Next, a solution of a photovoltaic element material including an electron donating organic material using a conjugated polymer having a structure represented by formula 1 and, if necessary, an electron accepting organic material, dissolved in an organic solvent is applied onto the transparent electrode to form an organic semiconductor layer. The organic solvent is not particularly limited as long as it can appropriately dissolve or disperse the electron donating organic material and the electron accepting organic material, but from the viewpoint of ease of handling, an organic solvent having a boiling point of 50° C. or higher is preferred.
[0058] Examples of methods for forming the organic semiconductor layer include spin coating, blade coating, slit die coating, screen printing, bar coater coating, mold coating, print transfer, immersion and pulling, inkjet, spray, and vacuum deposition. It is preferable to select a formation method according to the characteristics of the organic semiconductor layer to be obtained, such as film thickness control and orientation control. In addition, any additive that optimizes the phase separation structure of the organic semiconductor layer may be added. Preferred additives include 1,8-diiodooctane, 1-chloronaphthalene, and 1-phenylnaphthalene.
[0059] Next, a metal electrode (corresponding to the cathode in this case) such as Al is formed on the organic semiconductor layer by vacuum deposition or sputtering. When a low molecular weight organic material is used for the electron transport layer by vacuum deposition, it is preferable to continue forming the metal electrode while maintaining the vacuum.
[0060] When a hole transport layer is provided between the anode and the organic semiconductor layer, a solution of a desired p-type organic semiconductor material (such as PEDOT) is applied onto the anode, and then the solvent is removed to form a hole transport layer. Examples of the application method include spin coating, bar coating, and blade casting. Examples of the solvent removal method include heating using a vacuum thermostatic bath or a hot plate. When using a low molecular weight organic material such as a phthalocyanine derivative or a porphyrin derivative, it is also possible to apply a vacuum deposition method using a vacuum deposition machine.
[0061] When an electron transport layer is provided between the organic semiconductor layer and the cathode, a solution of a desired n-type organic semiconductor material (such as a fullerene derivative) or n-type inorganic semiconductor material (such as titanium oxide gel) is applied onto the organic semiconductor layer, and then the solvent is removed to form the electron transport layer. Examples of the application method and the solvent removal method include the methods exemplified for the formation of the hole transport layer. 60 When using a low molecular weight organic material such as the above, it is also possible to apply a vacuum deposition method using a vacuum deposition machine. EXAMPLES
[0062] (Synthesis example) The raw material, 2,2'-bistriisopropylsilyl-4,4'-dibromo-5,5'-bithiazole (compound 1), was synthesized with reference to Xugang Guo et al., Chemistry of Materials, 2018, Vol. 30, pp. 7988-8001.
[0063] [ka]
[0064] (Synthesis of compound 2) Compound 1 (5.5 g, 8.61 mmol) and tetrahydrofuran / acetic acid (720 mL / 900 mg) were added to a reaction vessel under an argon atmosphere, and the mixture was cooled to 0°C using an ice bath. Tetrabutylammonium fluoride (Tokyo Chemical Industry Co., Ltd.) (25.8 mL, 25.8 mmol) was added dropwise thereto, and the mixture was allowed to react for 1 hour. Water was added to the reaction solution, and the precipitated solid was collected by filtration. Compound 2 was obtained as a white solid by purifying it by recrystallization using a methanol solvent (2.43 g, yield 87%). The physical property data of the obtained compound 2 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.97(s,2H)
[0065] [ka]
[0066] (Synthesis of compound 4) The raw material, 2-(triisopropylsilyl)-5-tributylstannylthiophene (compound 3), was synthesized with reference to Victor Navarro-Fuster et al., Journal of Materials Chemistry, 2009, Vol. 19, pp. 6556-6567.
[0067] Under an argon atmosphere, compound 2 (2.30 g, 7.06 mmol), compound 3 (4.65 g, 8.77 mmol), tetrakis(triphenylphosphine)palladium(0) (Tokyo Chemical Industry Co., Ltd.) (203 mg, 0.175 mmol), and dimethylformamide (160 mL) were added to a reaction vessel and reacted at 90°C for 6 hours. After cooling to room temperature, water was added to the reaction solution and the precipitated solid was collected by filtration. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:dichloromethane (1:1) solvent as the mobile phase to obtain compound 4 as a pale yellow solid (1.69 g, 49% yield). The physical property data of the obtained compound 4 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.93(s,1H),σ=8.92(s,1H)σ=7.12-7.10(m,2H),σ=1.35-1.25(hept,3H),σ=1.09-1.06(d,18H)
[0068] [ka]
[0069] (Synthesis of Compound 5) Under an argon atmosphere, compound 4 (1.69 g, 3.48 mmol), palladium (II) acetate (Tokyo Chemical Industry Co., Ltd.) (78.1 mg, 10 mol%), tricyclohexylphosphonium tetrafluoroborate (Tokyo Chemical Industry Co., Ltd.) (256 mg, 20 mol%), cesium carbonate (Nacalai Tesque, Inc.) (2.27 g, 6.96 mmol), and 1,4-dioxane (400 mL) were added to a reaction vessel and reacted at 140°C for 10 hours. After cooling to room temperature, water was added to the reaction solution and the precipitated solid was filtered. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:dichloromethane (1:1) solvent as the mobile phase to obtain compound 5 as a pale yellow solid. (1.23 g, yield 87%) The physical property data of the obtained compound 5 are as follows: 1 HNMR (500MH z,CDCl3,TMS)σ=9.03(s,1H),σ=9.02(s,1H),σ=8.23(s,1H),σ=1.53-1.44(hept,3H),σ=1.19-1.17(d,18H)
[0070] [ka]
[0071] (Synthesis of compound 6) In an argon atmosphere, compound 5 (1.00 g, 2.47 mmol), 1,2-dibromo-1,1,2,2-tetrachloroethane (Tokyo Chemical Industry Co., Ltd.) (2.41 g, 7.41 mmol), and tetrahydrofuran (50 mL) were added to a reaction vessel and cooled to 0°C using an ice bath. Lithium hexamethyldisilazide (Sigma-Aldrich) (6.18 mL, 6.18 mmol) was added dropwise thereto and reacted for 15 minutes. Water was added to the reaction solution, and the mixture was extracted with chloroform, and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate, filtered, and the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (1:1) solvent as the mobile phase to obtain compound 6 as a white solid. (1.36 g, yield 97%) The physical property data of the obtained compound 6 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.16(s,1H),σ=1.55-1.44(hept,3H),σ=1.18-1.16(d,18H)
[0072] [ka]
[0073] (Synthesis of compound 8) The raw material 3-(2-ethylhexyl)-5-trimethylstannylthiophene (compound 7) can be synthesized with reference to Qichun Zhang et al., Journal of Materials Chemistry C, 2016, Vol. 4, pp. 3809-3814.
[0074] In an argon atmosphere, compound 6 (1.35 g, 2.40 mmol), compound 7 (1.98 g, 5.52 mmol), tetrakis(triphenylphosphine)palladium(0) (Tokyo Chemical Industry Co., Ltd.) (122 mg, 4.4 mol%), toluene (24 mL), and dimethylformamide (24 mL) were added to a reaction vessel and reacted at 90°C for 4 hours. After cooling to room temperature, water was added to the reaction solution and extracted with hexane, and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate and filtered, after which the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:ethyl acetate (20:1) solvent as the mobile phase to obtain compound 8 as a yellow liquid. (1.69 g, yield 90%) The physical property data of the obtained compound 8 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.22(s,1H),σ=7.53(d,2H),σ=7.10(q,2H),σ=2.62-2.58(t,4H),σ=1.66-1.59(m ,2H),σ=1.55-1.48(hept,3H),σ=1.38-1.23(m,16H),σ=1.22-1.19(m,18H),σ=1.15-0.74(m,12H)
[0075] [ka]
[0076] (Synthesis of Compound 9) Under an argon atmosphere, compound 8 (470 mg, 0.592 mmol) and chloroform (24 mL) were added to a reaction vessel, which was then shielded from light and cooled to 0°C using an ice bath. N-bromosuccinimide (Tokyo Chemical Industry Co., Ltd.) (211 mg, 1.18 mmol) was added thereto and reacted for 4 hours. Water was added to the reaction solution, which was then extracted with chloroform and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate and filtered, after which the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (3:1) solvent as the mobile phase to obtain compound 9 as a yellow solid. (507 mg, yield 90%) The physical property data of the obtained compound 9 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.17(s,1H),σ=7.34(s,1H),σ=7.34(s,1H),σ=2.58-2.52(dd,4H),σ=1.72-1.65(d d,2H),σ=1.58-1.47(hept,3H),σ=1.41-1.28(m,16H),σ=1.23-1.20(m,18H),σ=0.95-0.89(m,12H)
[0077] [ka]
[0078] (Synthesis of compound 10) Compound 9 (680 mg, 0.723 mmol) and tetrahydrofuran (60 mL) were added to a reaction vessel under an argon atmosphere, and the mixture was cooled to 0°C using an ice bath. Tetrabutylammonium fluoride (Tokyo Chemical Industry Co., Ltd.) (1.09 mL, 1.09 mmol) was added dropwise thereto, and the mixture was allowed to react for 1 hour. Water was added to the reaction solution, which was then extracted with chloroform, and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate, filtered, and the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (3:1) solvent as the mobile phase, to obtain compound 10 as a pale yellow solid. (539 mg, yield 94%) The physical property data of the obtained compound 10 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=7.98-7.96(d,1H),σ=7.60-7.59(d,1H),σ=7.25-7.24(d,2H),σ=2. 56-2.49(dd,4H),σ=1.72-1.62(m,2H),σ=1.43-1.25(m,16H),σ=0.98-0.87(m,12H)
[0079] [ka]
[0080] (Synthesis of compound 11a) Lithium diisopropylamide (LDA) (0.6M, 0.632mL, 0.377mL) was prepared in a reaction vessel under an argon atmosphere and cooled to -78°C. Compound 10 (150mg, 0.189mmol) dissolved in tetrahydrofuran (9.44mL) was added dropwise thereto and reacted for 30 minutes. 2-Ethylhexanal (96.8mg, 0.755mmol) was added dropwise to the reaction solution and allowed to return to room temperature overnight. Dilute hydrochloric acid was added to the reaction solution, which was extracted with hexane, and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate and filtered, after which the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:ethyl acetate (20:1) solvent as the mobile phase to obtain compound 11a as a yellow solid. (153mg, yield 88%) The physical property data of the obtained compound 11a are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=7.84-7.81(m,1H),σ=7.31(s,1H),σ=7.30(s,1H),σ=5.14-5.10(t,1H), σ=2.57-2.52(d,5H),σ=1.72-1.63(m,2H),σ=1.43-1.24(m,24H),σ=0.99-0.82(m,18H)
[0081] (Synthesis of compound 11b) Compound 11b was obtained as a pale yellow liquid (89.0 mg, yield 75%) by synthesizing it in the same manner as compound 11a, except that 2-ethylhexanal was replaced with 3-ethylheptanal. The physical property data of the obtained compound 11b are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=7.91(m,1H),σ=7.34(s,1H),σ=7.33(s,1H),σ=5.24-5.20(d,1H),σ=2.58-2.52( dd,4H),σ=2.17-1.84(m,2H),σ=1.71-1.64(m,2H),σ=1.39-1.24(m,25H),σ=0.97-0.84(m,18H)
[0082] [ka]
[0083] (Synthesis of compound 12) Under an argon atmosphere, LDA (0.6M, 1.6mL, 0.956mL) was prepared in a reaction vessel and cooled to -78°C. Compound 10 (380mg, 0.478mmol) dissolved in tetrahydrofuran (23.9mL) was added dropwise thereto and reacted for 30 minutes. Carbon dioxide gas was bubbled into the reaction solution. Dilute hydrochloric acid was added to the reaction solution, and the precipitated solid was collected by filtration to obtain compound 12 as a yellow solid. The obtained compound 12 was used in the next reaction without purification.
[0084] [ka]
[0085] (Synthesis of compound 13) Compound 11a (50 mg, 0.0542 mmol), triethylsilane (12.6 mg, 0.108 mmol), trifluoroacetic acid (55.6 mg, 0.48 mmol), and dehydrated dichloromethane (0.62 mL) were added to a reaction vessel under an argon atmosphere, and the mixture was allowed to react at room temperature for 3 hours. A saturated aqueous solution of sodium bicarbonate was added to the reaction solution, and the mixture was extracted with dichloromethane, and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate and filtered, after which the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (3:1) solvent as the mobile phase, to obtain compound 13 as a yellow solid. (34.7 mg, yield 71%) The physical property data of the obtained compound 13 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=7.71(s,1H),σ=7.33(s,1H),σ=7.32(s,1H),σ=2.98(d,2H),σ=2.55 (d,4H),σ=1.78(m,1H),σ=1.68(m,2H),σ=1.50-1.30(m,24H),σ=0.98-0.88(m,18H)
[0086] [ka]
[0087] (Synthesis of compound 14) Compound 11b (68 mg, 0.0726 mmol), pyridinium dichromate (81.9 mg, 0.218 mmol), and chloroform (3.63 mL) were added to a reaction vessel under an argon atmosphere, and the mixture was allowed to react at 50° C. overnight. The reaction solution was filtered, and the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (3:1) solvent as the mobile phase, to obtain compound 14 as a yellow solid (89.0 mg, yield 75%). The physical property data of the obtained compound 14 are as follows: 1 HNMR (500MH z,CDCl3,TMS)σ=8.60(s,1H),σ=7.36(s,1H),σ=7.35(s,1H),σ=3.10-3.01(d,2H),σ=2.60-2.52( dd,4H),σ=2.23-2.10(m,1H),σ=1.76-1.63(m,2H),σ=1.51-1.25(m,24H),σ=1.41-0.78(m,18H)
[0088] [ka]
[0089] (Synthesis of compound 15) Compound 12 (50 mg, 0.0596 mmol), potassium carbonate (24.7 mg, 0.179 mmol), and dimethylformamide (3.97 mL) were added to a reaction vessel under an argon atmosphere, and 2-ethylhexyl bromide (17.3 mg, 0.0894 mmol) was added dropwise at room temperature, followed by reaction at 90°C overnight. Water was added to the reaction solution, which was then extracted with hexane and the organic layer was washed with water. The organic layer was dried over anhydrous sodium sulfate and filtered, after which the solvent was distilled off under reduced pressure. The resulting reaction mixture was separated and purified by silica gel column chromatography using a hexane:chloroform (3:1) solvent as the mobile phase to obtain compound 15 as a yellow solid (37.0 mg, yield 65%). The physical property data of the obtained compound 15 are as follows: 1 HNMR (500MH z ,CDCl3,TMS)σ=8.67(s,1H),σ=7.31(s,1H),σ=7.31(s,1H),σ=4.37-4.27(m,2H),σ=2.57-2.53(d,4H),σ=1. 85-1.73(hept,1H),σ=1.73-1.62(m,2H),σ=1.57-1.43(m,6H),σ=1.41-1.29(m,18H),σ=1.05-0.87(m,18H)
[0090] [ka]
[0091] Example 1 (Synthesis of conjugated polymer P1) Compound 15 (47.6 mg, 0.05 mmol), compound 16 (45.3 mg, 0.05 mmol), tetrakis(triphenylphosphine)palladium(0) (Tokyo Chemical Industry Co., Ltd.) (1.15 mg, 2 mol%), and toluene (2.0 mL) were added to a reaction vessel, and the mixture was reacted at 200 ° C. for 2 hours using a microwave reactor (Biotage, Initiator). After cooling to room temperature, the reaction mixture was added to methanol (50 mL), stirred for 2 hours, filtered, and then Soxhlet extraction was performed using methanol, hexane, and dichloromethane as solvents to remove low molecular weight components. The residue was extracted with chloroform, and the solvent was distilled off under reduced pressure, followed by adding methanol and filtering to obtain conjugated polymer P1 as a red solid. (51 mg, yield 74%, number average molecular weight: 91,000, molecular weight dispersity: 1.9). The number average molecular weight was calculated as a standard polystyrene equivalent molecular weight using HLC-8321GPC / HT manufactured by Tosoh Corporation.
[0092] (Preparation and evaluation of solar cell element using conjugated polymer P1) The glass substrate on which the ITO film was patterned was ultrasonically cleaned for 10 minutes with neutral detergent, ion-exchanged water, acetone, and isopropyl alcohol, and then UV ozone treatment was performed. Next, an aqueous dispersion of poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonic acid) (Clevios® P VP Al 4083, manufactured by Heraeus) was spin-coated at 4000 rpm for 30 seconds. The substrate was heated at 150°C for 15 minutes to form a hole extraction layer. The substrate on which the hole extraction layer was formed was brought into a glove box, and the conjugated polymer P1 and the n-type material L8-BO were spin-coated by a sequential coating method to form a photoactive layer (film thickness 100 nm). Furthermore, a methanol solution (1 mg / mL, 0.5% acetic acid added) of poly[[2,7 bis-(2-ethylhexyl)-1,3,6,7,8-hexahydro-1,3,6,8-tetraoxobenzo[lmn][3,8]phenanthroline-4,9-diyl]-2,5-thiophenediyl[9,9-bis[3-(dimethylamino)propyl]-9H-fluorene-2,7-diyl]-2,5-thiophenediyl]] was spin-coated on the photoactive layer as an electron extraction layer at 2000 rpm for 60 seconds. Next, a 150 nm thick silver film was formed as an electrode layer by a resistance heating vacuum deposition method, and a 4 mm square organic thin-film solar cell element was fabricated.
[0093] The obtained organic thin-film solar cell was subjected to a solar simulator (XES-40S1, manufactured by SAN-EI Electric Co., Ltd.) (AM1.5G filter, irradiance 100 mW / cm 2 The generated current and voltage were measured by irradiating a constant amount of light using a 1000-millimeter-wave irradiator. Figure 2 shows the current density-voltage characteristics, and Figure 3 shows the spectral sensitivity characteristics.
[0094] From the obtained Figure 1, the short circuit current density Jsc (mA / cm 2 ), open circuit voltage Voc (V), and form factor FF were calculated, and Jsc = 24.8 mA / cm 2 , Voc = 0.92 V, and FF = 0.75. The photoelectric conversion efficiency (η) was calculated from the formula η = (Jsc × Voc × FF) / 100 and was found to be 17.0%.
[0095] [ka]
[0096] Example 2 (Synthesis of conjugated polymer P2) Conjugated polymer P2 was obtained as a red solid by synthesizing it in the same manner as conjugated polymer P1 (48 mg, yield 71%, number average molecular weight: 51,000, molecular weight dispersity: 2.0).
[0097] (Preparation and evaluation of solar cell elements using conjugated polymer P2) An organic thin-film solar cell (film thickness 100 nm) was fabricated in the same manner as the solar cell element using the conjugated polymer P1 described above, except that the conjugated polymer P2 and the n-type material Y6 were spin-coated by the sequential coating method to form a photoactive layer, and its characteristics were evaluated. The current density-voltage characteristics shown in Figure 4 were obtained, with Jsc = 22.4 mA / cm. 2 , Voc = 0.93 V, FF = 0.66. η was 13.8%. Figure 5 shows the spectral sensitivity characteristics.
[0098] [ka]
[0099] Comparative Example 1 (Synthesis of conjugated polymer P3) Conjugated polymer P3 was obtained as a red solid by synthesizing it in the same manner as conjugated polymer P1 (63 mg, yield 95%, number average molecular weight: 70,000, molecular weight dispersity: 2.3).
[0100] (Preparation and evaluation of solar cell elements using conjugated polymer P3) An organic thin-film solar cell (film thickness 100 nm) was fabricated in the same manner as the solar cell element using the conjugated polymer P1 described above, except that the conjugated polymer P3 and the n-type material Y6 were spin-coated by the successive coating method to form a photoactive layer, and its characteristics were evaluated. The current density-voltage characteristics shown in Figure 6 were obtained, with Jsc = 24.9 mA / cm. 2 , Voc = 0.85 V, FF = 0.63. η was 13.5%. Figure 7 shows the spectral sensitivity characteristics.
[0101] The evaluation results of Examples 1 and 2 and Comparative Example 1 are summarized in Table 1. It can be seen that the organic thin-film solar cells prepared using the conjugated polymers P1 and P2 having a thienobenzobisthiazole skeleton into which an electron-withdrawing group has been introduced have a higher open-circuit voltage and better characteristics than the organic thin-film solar cell prepared using the conjugated polymer P3.
[0102] [Table 1] [Industrial Applicability]
[0103] The conjugated polymer according to the present invention exhibits p-type semiconductor properties and can be used as an electron-donating organic semiconductor material (donor material) for photovoltaic devices.
Claims
1. Having a structure represented by formula 1: 【Chemistry 1】 (In formula 1, R 1 R represents an alkyl group or an alkoxy group. 2 ~R 6 may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkanoyl group, an alkoxycarbonyl group, a halogen, an aryl group, or a heteroaryl group. A represents an arylene group or a heteroarylene group. x and y may be the same or different and represent an integer of 0 to 4. When x or y is 2 or more, x R 3 and R 4 , y R 5 and R 6 may be the same or different. n represents the degree of polymerization, and is in the range of 2 to 1,000. A conjugated polymer comprising:
2. In the above formula 1, R 2 ~R 6 is hydrogen, a halogen or an alkyl group; The conjugated polymer according to claim 1 .
3. In the formula 1, A has a benzodithiophene structure. The conjugated polymer according to claim 1 .
4. Having a structure represented by formula 2: 【Chemistry 2】 (In formula 2, R 7 R represents an alkyl group or an alkoxy group. 8 ~R 10 may be the same or different and represent hydrogen, an alkyl group, an alkoxy group, an alkoxycarbonyl group, a halogen atom, an aryl group, or a heteroaryl group. A conjugated compound characterized in that:
5. The conjugated polymer according to any one of claims 1 to 3 is included.
1. An electron-donating organic material comprising:
6. The present invention relates to an organic compound having an electron donating organic material and an electron accepting organic material. A material for a photovoltaic device, comprising:
7. The electron-accepting organic material includes a non-fullerene type electron-accepting organic material. The material for a photovoltaic device according to claim 6 .
8. A photovoltaic element having at least an anode and a cathode, the photovoltaic element having an organic power generation layer between the anode and the cathode, the photovoltaic element comprising the material for photovoltaic elements according to claim 6. A photovoltaic element characterized by:
9. A photovoltaic element having at least an anode and a cathode, the photovoltaic element having an organic power generation layer between the anode and the cathode, the photovoltaic element comprising the material for photovoltaic elements according to claim 7. A photovoltaic element characterized by:
Citation Information
Patent Citations
Conjugated polymer, conjugated compound, and electron-donating organic material, photovoltaic device material and photovoltaic device that employ the same
JP2023031215A